Distribution of Inheritance of Joint Property in Indonesian Legal Pluralism: Inter-Legal System Dialogue Toward a Fair Regulatory Framework - Moh Arifin; Gunarto; Bambang Tri Bawono; Afif Noor; Kiki Nuriska Denhas (Universitas Negeri Semarang, 2026)
The distribution of inheritance of joint property in the context of succession is one of the issues requiring special attention in Indonesia's pluralistic legal system, which recognizes and applies state law, Islamic law, and customary law. This legal pluralism often results in differing interpretations regarding the status of marital joint property, the rights of the surviving spouse, and the rights of heirs, leading to legal uncertainty and social conflict. This study analyses the distribution of joint property from the perspective of Indonesian legal pluralism. It proposes a fairer regulatory framework, based on the analysis of the Kendal Religious Court Decision No. 838/Pdt.G/2023/PA.Kdl. Employing doctrinal (normative juridical) research, this study qualitatively analyzes primary and secondary legal materials grounded in legal pluralism and interlegality theory, Gustav Radbruch’s theory of the purpose of law, John Rawls’s theory of justice, and the principle of maqāṣid al-sharīʿah. The findings show that the Kendal Religious Court has applied the Compilation of Islamic Law and the Marriage Law to fulfill legal certainty; however, its legal considerations remain normatively oriented and have not optimally integrated substantive justice and the realities of life in a pluralistic legal context. This study proposes an integrative regulatory framework that harmonizes state law, Islamic law, and customary law, as well as harmonizes Islamic law with other legal systems, not as rivalrous competition but as a dialogue that safeguards the rights of all heirs. Thus, it is expected that court decisions will create legal certainty, justice, and benefits in Indonesia’s multicultural and multireligious society.